Pengaruh Kompetensi Dan Kompensasi Terhadap Kinerja Pegawai Primer Koperasi - Arman Maulana (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
This study aims to analyze the Effect of Competence and Compensation on the Performance of Cooperative Primary Employees in the Koperasi Primer Kartika Artileri Berdaya Guna Sepanjang Masa Pusat Kesenjataan Artileri Medan Kota Cimahi. The results of the study show that competence and compensation simultaneously influence and significantly affect employee performance. Partially, the competency variable on employee performance has a significant effect, then for compensation variables on employee performance a significant effect is obtained. Thus if good competence with the field of work is carried out, and also supported by the provision of good compensation given to employees, then employees will always be able to provide optimal work results for an organization.